CIRSE Standards of Practice for the Classification of Complications: The Modified CIRSE Classification System - Filippiadis, D. K.; Pereira, Philippe L.; Hausegger, K. A.; Ryan, A. G.; Binkert, C. A. (CardioVascular and interventional radiology, 2026)
The CIRSE classification system was published in 2017 aiming to standardize the reporting of complications by avoiding subjective definitions and an excessive number of grades. The original system described 6 grades: Grade 1: complication could be solved within the same procedure, Grade 2: unplanned prolonged hospitalization < 48 h without an additional therapy, Grade 3: additional therapies needed or hospitalization > 48 h, but no sequelae, Grade 4: mild sequelae beyond hospitalization, Grade 5: severe sequelae requiring assistance in daily life, and Grade 6: death. Following initial evaluation through a validation process performed during the International Conference on Complications in Interventional Radiology (ICCIR 2023), a need to modify the system was identified, specifically to stratify grades 1 and 3 based on the degree of impact on the patient in terms of success or failure of the procedure (Grade 1) and on the duration of hospital stay (Grade 3). Thus, Grade 1 was subdivided into 1a and 1b: 1b describing situations when the complication was resolved within the same procedure, but the intended procedure was not completed and Grade 3 subdivided into 3a: Hospital stay > 48 h, but < 2 weeks and 3b > 2 weeks to depict the complications that resulted in the most time- and resource consuming hospitalizations. It remained the case that no permanent sequelae are observed in grade 3. This initial testing of the modified classification system in an international IR complication meeting showed high reliability and strong inter-observer agreement. The modified CIRSE system for classification of complications addresses the shortcomings of the original system while remaining easy to use with clear and objective parameters describing the clinical outcomes after a complication.